PENDIDIKAN KESEHATAN MENUJU REMAJA SEHAT BEBAS ANEMIA - Prastiwi, Dani; Isrofah, Isrofah; Vianti, Remilda Armika; Meiliani, Siska Ayu; Amanda, Putri; Husna, Askia Azminatul (LPPM Institut Pendidikan Nusantara Global, 2024)
Anemia often occurs in teenage girls. Lack of knowledge and awareness in efforts to prevent anemia are factors causing the high incidence of anemia in adolescents. There are many impacts that occur when anemia is left untreated, and can even have long term impacts. This community service activity uses a participant active learning approach with interactive lecture and discussion methods focusing on health education about anemia with 80 participants. The result of this health education activity is an increase in participants knowledge. The hope is that participants can apply the knowledge gained in everyday life, such as consuming balanced nutricious food, doing regular physical activity and taking blood suplement tablets.